Doctor I. Bernard Weinstein (1930-2008) - Saxe Einbond, Linda (European Journal of Oncology and Environmental Health, 2008)
It is with great sorrow that the scientific and medical communities mourn the passing of remarkable scientist, teacher, scholar, mentor, and friend, Dr I. Bernard Weinstein. Dr Weinstein, a worldrenowned authority on the prevention and treatment of cancer, exemplified the goals and tenets of the Collegium Ramazzini...